CORPORATE GOVERNANCE AND SUSTAINABILITY REPORT DISCLOSURE UNDER MANDATORY REPORTING: EVIDENCE FROM INDONESIAN ENERGY COMPANIES - Shafira Hanun Maharani; Niswah Baroroh (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
This study aims to analyze the effect of majority ownership, board of directors, and environmental costs on sustainability report disclosure, while also examining the moderating role of financial slack in these relationships. The population of this research was energy companies listed on the IDX during 2022-2024, totaling 75 companies. The purposive sampling technique was employed to select the sample. Due to the use of an unbalanced panel dataset, the number of observations varied across years, resulting in a total of 90 observations as the units of analysis. The data were analyzed using a panel data estimation technique known as the Random Effects Model. The study findings revealed that the board of directors has a positive effect on sustainability report disclosure, but the majority ownership and environmental cost have no effect on sustainability report disclosure. Financial slack as a moderating variable does not have an effect on the relationship between sustainability report disclosure and independent variables, namely majority ownership, board of directors, and environmental cost. The findings indicate that, within a mandatory sustainability reporting framework, corporate sustainability disclosure is more strongly influenced by governance mechanisms and regulatory compliance than by firm specific financial conditions. These results also indicate that the variables examined in this study are not sufficient to fully explain variations in sustainability report disclosure, implying the presence of other influencing factors. This study contributes to the existing literature by providing empirical evidence that internal financial resources and majority ownership have limited explanatory power in explaining sustainability reporting practices under a mandatory reporting system in the Indonesian energy sector.